South Atlantic Coral Reefs Are Major Global Warming Refugia and Less Susceptible to Bleaching - Mies, Miguel; Francini-Filho, Ronaldo B.; Zilberberg, Carla; Garrido, Amana G.; Longo, Guilherme O.; Laurentino, Eduarda; Güth, Arthur Z.; Sumida, Paulo Y. G.; Banha, Thomás N. S. (Frontiers in Marine Science, 2020)
Mass coral bleaching has increased in intensity and frequency and has severely impacted shallow tropical reefs worldwide. Although extensive investigation has been conducted on the resistance and resilience of coral reefs in the Indo-Pacific and Caribbean, the unique reefs of the South Atlantic remain largely unassessed. Here we compiled primary and literature data for reefs from three biogeographical regions: Indo-Pacific, Caribbean and South Atlantic and performed comparative analyses to investigate whether the latter may be more resistant to bleaching. Our findings show that South Atlantic corals display critical features that make them less susceptible to mass coral bleaching: (i) deeper bathymetric distribution, as species have a mean maximum depth of occurrence of 70 m; (ii) higher tolerance to turbidity, as nearly 60% of species are found in turbid conditions; (iii) higher tolerance to nutrient enrichment, as nitrate concentration in the South Atlantic is naturally elevated; (iv) higher morphological resistance, as massive growth forms are dominant and comprise two thirds of species; and (v) more flexible symbiotic associations, as 75% of corals and 60% of symbiont phylotypes are generalists. Such features were associated with occurrence of fewer bleaching episodes with coral mortality in the South Atlantic, approximately 60% less than the Indo-Pacific and 50% less than the Caribbean. In addition, no mass coral mortality episodes associated with the three global mass bleaching events have been reported for the South Atlantic, which suffered considerably less bleaching. These results show that South Atlantic reefs display several remarkable features for withstanding thermal stress. Together with a historic experience of lower heat stress, our findings may explain why climate change impacts in this region have been less intense. Given the large extension and latitudinal distribution of South Atlantic coral reefs and communities, the region may be recognized as a major refugium and likely to resist climate change impacts more effectively than Indo-Pacific and Caribbean reefs.